Pengaruh Kehadiran dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Indomaret Di Sidoarjo (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the extent to which competence, professional attitudes, and oversight mechanisms influence the quality of financial reporting within local government institutions. The research was conducted in regional government agencies (OPDs) located in the Selayar Islands Regency using a quantitative approach. Data were collected through questionnaires distributed to 64 respondents and analyzed using multiple linear regression techniques. The findings indicate that competence, professionalism, and oversight all have a significant impact on the quality of financial reporting. These results highlight the critical role of enhancing human resource capabilities and strengthening supervisory functions to ensure the production of transparent, accurate, and reliable financial reports in the public sector.